A Simple Field-cum-laboratory Method of Determining Soil Permeability - Seth, S. K.; Yadav, J. S. P. (Indian Forester, 1958)
An apparatus designed for a field-cum-laboratory method, wherein undisturbed soil columns taken in the field can be used for determining soil permeability in the laboratory, has been described in detail. Permeability data for soils of the Demonstration Area at the Forest Research Institute, Dehra Dun have been reported. The method has proved to be simple, accurate and easily workable, and is recommended for adoption with advantage in studies of hydraulic conductivity, particularly of forest soils.